2019
DOI: 10.1007/s10658-019-01827-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Alternaria spp. as causal agent of dead flower buds disease of pear (Pyrus communis) in the Netherlands and methods for disease control

Abstract: The occurrence of dead dormant flower buds is a common phenomenon of economic importance in the major pear production areas of Europe. Thus far, the cause of dead flower buds disease remained unknown. Several causes have been proposed, including insufficient tree chilling, unmet dormancy requirements, incompatibility between scion and cultivar, but also various biotic stress agents such as pathogens and pests. In this study, we tested the relationship between reduction of tree growth and dead flower bud incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…This is supported by previous studies on the wounding of plant tissues with Alternaria spp. [ 72 ]; wounding was shown in this study to be an important disease factor affecting the South African pecan industry. Nonetheless, a previous study [ 56 ] also showed that insects can cause wounding on pecans in South Africa, which contributed to the dissemination of fungal pathogens such as A. alternata .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This is supported by previous studies on the wounding of plant tissues with Alternaria spp. [ 72 ]; wounding was shown in this study to be an important disease factor affecting the South African pecan industry. Nonetheless, a previous study [ 56 ] also showed that insects can cause wounding on pecans in South Africa, which contributed to the dissemination of fungal pathogens such as A. alternata .…”
Section: Discussionmentioning
confidence: 83%
“…This is also an indication that stress factors could play a role in the overall health of pecan trees [ 35 ]. This has been shown in other plants or crops, such cotton ( Gossypium hirsutum ) leaf senescence in China [ 74 ], cruciferous vegetables in Europe [ 68 ], and more recently on pear ( Pyrus communis ) in the Netherlands [ 72 ]. Control and management are challenging as A. alternata can only be eradicated systemically [ 75 ], and even harvested pecan nuts-in-shucks and kernels that appear healthy at this point can subsequently start showing symptoms due to endophytes such as A. alternata during storage and transport [ 76 ].…”
Section: Discussionmentioning
confidence: 96%
“…Alternaria spp. pode colonizar partes de flores durante a floração e após a queda das pétalas, mas devido ao longo período de incubação, a doença não se desenvolve até que o fruto se torne suscetível durante um longo armazenamento (WENNEKER et al, 2019).…”
Section: Controle De Fungosunclassified